The Development of the Argentine Automobile Industry in the Age of Globalization - Wójtowicz, Mirosław (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2013)
The aim of this paper is to determine the transformation of the production potential of theArgentine automotive industry in the years 1952-2011. The evolution of production and investmentstrategies of the international automotive companies were also examined, considering changes in theindustrial policy, progressing globalization and integration within Mercosur. The origins of this industryin Argentina were associated with acceleration of industrialization and modernization under therule of Juan Peron administration. Developed behind the “cover” of high tariffs, the automobile industryhas contributed to the modernization and transformation of the economic structure of the country.The studied period can be divided into three main phases of development. The first phase (1952-1975) is associated with the introduction of the automobile industry to Argentina, which initially took placeunder the heavy involvement of the state and private capitals. Its second stage was characterized bythe consolidation of the companies operating in the country with the decisive role played by transnationalcorporations. The second phase (1976-1990) covers the years of deep crisis in this sector, whichwas the outcome of the unfavorable economic situation in the country and wrong industrial policyliberalizing imports of finished vehicles. This led not only to the decrease in the number of producedvehicles, but also some of the automobile companies opted to leave the country. During the third phase(1991-2011) the auto sector witnessed a rapid increase in production, which reached the highest pointin the history in 2011. This success was attained due to export-oriented policy in this sector, which tookadvantage of the creation of Mercosur.